2020
DOI: 10.3390/cancers12041059
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Occult Lymph Node Metastasis in Primary Larynx Squamous Cell Carcinoma, by Subsite, T Classification and Neck Level: A Systematic Review

Abstract: Background: Larynx cancer is a common site for tumors of the upper aerodigestive tract. In cases with a clinically negative neck, the indications for an elective neck treatment are still debated. The objective is to define the prevalence of occult metastasis based on the subsite of the primary tumor, T classification and neck node levels involved. Methods: All studies included provided the rate of occult metastases in cN0 larynx squamous cell carcinoma patients. The main outcome was the incidence of occult met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 73 publications
2
29
1
2
Order By: Relevance
“…On multivariable logistic regression, tumor site, tumor size and histological grade were associated with significantly greater odds of lymph nodes metastasis. Consistent with most studies, supraglottic cancer was a risk factor for lymph node metastasis, 15,19,20 whose relative risk of lymph node metastasis was close to 3 times that of glottic cancer. For poorly differentiated laryngeal cancer, the possibility of lymph node metastasis was significantly higher than that of welldifferentiated cancer, 14,20 and the relative risk of lymph node metastasis was twice that of well-differentiated laryngeal cancer.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On multivariable logistic regression, tumor site, tumor size and histological grade were associated with significantly greater odds of lymph nodes metastasis. Consistent with most studies, supraglottic cancer was a risk factor for lymph node metastasis, 15,19,20 whose relative risk of lymph node metastasis was close to 3 times that of glottic cancer. For poorly differentiated laryngeal cancer, the possibility of lymph node metastasis was significantly higher than that of welldifferentiated cancer, 14,20 and the relative risk of lymph node metastasis was twice that of well-differentiated laryngeal cancer.…”
Section: Discussionsupporting
confidence: 78%
“…For patients with laryngeal cancer, the more advanced the T classification gets, the greater possibility of lymph node metastasis there is. [12][13][14][15] Positive cervical lymph nodes have a negative impact on the patient's prognosis, and LND for such patients can improve survival significantly. 16 Similarly, our study also showed that the survival of elderly patients with laryngeal cancer (including OS and CSS) with lymph node metastasis was significantly inferior to that of patients without metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases (LNMs) are common at the time of diagnosis in head and neck squamous cell carcinomas (HNSCCs), while the rate of occult LNMs is up to 20% in some subtypes of HNSCC [ 1 , 2 , 3 , 4 , 5 ]. The presence of LNMs bears a major prognostic influence, with an estimated 50% reduction in overall survival in nodal negative vs. nodal positive HPV-negative HNSCC [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal cancer remains the second most common malignant tumor of the upper respiratory tract. 1 Supraglottic cancer (SC), which accounts for 30%-40% of patients with laryngeal cancers, is characterized by a high rate of lymph node metastases, even in earlystage tumors (T1-2). 2 The high lymph node metastasis rate contributes to a worse prognosis in SC than with glottic cancer.…”
Section: Introductionmentioning
confidence: 99%